Syakhsiyyatu al-Ab al-Misali fi Qissati Luqman al-Hakim ‘inda Sayyid Qutb fi Kitabihi at-Tafsir Fi Zilali al-Qur`an: Sayyid Qutb on The Character of The Ideal Father in The Story of Luqman al-Hakim in Tafsir Fi Zilal Al-Qur`an - Asif Trisnani; Uly Ariana Sari; Muhammad Thoriqul Islam (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2025)
The father significantly influences the quality of connections within the family unit. Despite bearing considerable duties, his presence frequently goes unrecognized, especially by children. The Qur’an delineates the attributes of an exemplary father through diverse narratives, notably the account of Luqman al-Hakim—a sagacious being endowed with insight by Allah SWT, albeit not a prophet. The narrative, located in Surah Luqman verses 12–19, imparts moral lessons and ideals relevant to modern life. This study investigates the Qur’anic depiction of parenthood through an analysis of Luqman’s counsel to his son, with the objective of elucidating the fundamental characteristics of an exemplary father. The study employs a library-based approach and descriptive analysis, concentrating on Sayyid Qutb's interpretation in Fi Zilal al-Qur'an. Research indicates that Luqman epitomizes the quintessential paternal archetype through four principal responsibilities. Initially, he assumes the role of an educator, fostering his child with affection and comprehension. Secondly, he functions as a sagacious advisor, providing counsel grounded in religious principles. Third, he serves as a role model, somebody whom youngsters might admire and ultimately imitate. Ultimately, he assumes the position of family leader, bearing the duty for the household's spiritual and moral guidance. This research underscores the necessity of acknowledging and revitalizing the father's significant role in familial dynamics, utilizing the narrative of Luqman al-Hakim as a perennial exemplar of fostering responsible and value-oriented parenting.